2016
DOI: 10.1002/nag.2551
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of influence of particle characteristics on the non‐coaxiality of anisotropic granular materials using DEM

Abstract: Summary As a result of deposition process and particle characteristics, granular materials can be inherently anisotropic. Many researchers have strongly suggested that the inherent anisotropy is the main reason for the deformation non‐coaxiality of granular materials. However, their relationships are not unanimous because of the limited understanding of the non‐coaxial micro‐mechanism. In this study, we investigated the influence of inherent anisotropy on the non‐coaxial angle using the discrete element method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…This poses challenges for the description of granular materials as a (plastic) continuum, where the usual assumption of stress and strain coaxiality is required to formulate the constitutive closures [Hill, 1950]. Noncoaxiality between contact or shape, and force, normals arises through interactions involving grain-scale properties such as variable shape and friction [Ai et al, 2014;Jiang et al, 2017;Zhao and Guo, 2015], perhaps similar to noncoaxiality observed in simulations of melt-present processes in the Earth's mantle with viscosity heterogeneity [Butler, 2012;Katz et al, 2006]. To quantify this anisotropy, a description of the microstructure is required.…”
Section: Microstructure: Fabric Tensors and Anisotropymentioning
confidence: 99%
“…This poses challenges for the description of granular materials as a (plastic) continuum, where the usual assumption of stress and strain coaxiality is required to formulate the constitutive closures [Hill, 1950]. Noncoaxiality between contact or shape, and force, normals arises through interactions involving grain-scale properties such as variable shape and friction [Ai et al, 2014;Jiang et al, 2017;Zhao and Guo, 2015], perhaps similar to noncoaxiality observed in simulations of melt-present processes in the Earth's mantle with viscosity heterogeneity [Butler, 2012;Katz et al, 2006]. To quantify this anisotropy, a description of the microstructure is required.…”
Section: Microstructure: Fabric Tensors and Anisotropymentioning
confidence: 99%
“…Some studies (Kung et al, 2007;Kung et al, 2009;Schädlich and Schweiger, 2012), have innovatively considered the small strain stiffness behavior of soils and obtained accurate predictions. In addition, due to its natural deposition, the soil always exhibits naturally inherent cross-anisotropy of elasticity (Jiang et al, 2016a;Jiang et al, 2017), which has a significant effect on lateral wall deflection and ground movement in an excavation (Jiang et al, 2016b;Teng et al, 2014). Due to the integrity that exists between the soil and the structure in an excavation, associating the structures' parameters (e.g., stiffness of the diagram wall, of supporting structures) with the soil parameters in the optimization could give more accurate predictions of the wall and ground responses.…”
Section: Introductionmentioning
confidence: 99%